The right to die according to Hans Jonas - Tambou Kamgue, Ericbert (2022)
Since the XVIII century, we have witnessed a concealment of death in western society. From now on, the discourse on death is the responsibility of medicine, which gives it technical answers; which contributes to the medicalization of the end of life. Faced with suffering, anguish and loneliness, the act of shortening life seems, therefore, the only solution to help the patient. From there arises a certain right, “the right to die” or “the right to die with dignity”. What does the right to die mean? Can we talk of a right when it comes to death? Faced with an incurable patient or at the end of life, is the ethical and medical question to deliberately kill him or take care of him? This article aims to reflect with Jonas on the “right to die” and highlight his ethical and medical involvement in the care of patients at the end of life. According to Jonas, the right to die represents an extreme in the scope of medical practices and is a call to seek the best humane and dignified conditions for a life that is about to end.